2002
DOI: 10.1073/pnas.262525399
|View full text |Cite
|
Sign up to set email alerts
|

Modularity and reshuffling of Snail and Slug expression during vertebrate evolution

Abstract: Gene duplication has been a major mechanism for increasing genomic complexity and variation during evolution. The evolutionary history of duplicated genes has been poorly studied along the vertebrate lineage. Here, we attempt to study that history by analyzing the expression of two members of the Snail family, Snail and Slug, in representatives of the major vertebrate groups. We find a surprising degree of variability in a subset of the expression sites for both genes in different species. Although some of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 48 publications
3
83
0
Order By: Relevance
“…This PDGFR␣ ϩ mesenchymal population exhibits low-level, cytoplasmically localized E-cadherin immunoreactivity. The reduced E-cadherin immunoreactivity in the cytoplasm of these PDGFR␣ ϩ cells is consistent with the reports of Snail/Slug-induced repression of E-cadherin synthesis (Cano et al, 2000;Locascio et al, 2002), coupled with endocytosis-mediated turnover of cadherin from the cell surface (see Miller and McClay, 1997). Importantly, the pattern of dual immunoreactivity by such subepithelial cells clearly indicates that they originate from the overlying E-cadherin ϩ non-neural epithelium and that they lose epithelial morphology as a consequence of E-cadherin down-regulation from their cell surfaces.…”
Section: Non-neural Epithelium In the Neural Fold Appears To Be A Sousupporting
confidence: 91%
“…This PDGFR␣ ϩ mesenchymal population exhibits low-level, cytoplasmically localized E-cadherin immunoreactivity. The reduced E-cadherin immunoreactivity in the cytoplasm of these PDGFR␣ ϩ cells is consistent with the reports of Snail/Slug-induced repression of E-cadherin synthesis (Cano et al, 2000;Locascio et al, 2002), coupled with endocytosis-mediated turnover of cadherin from the cell surface (see Miller and McClay, 1997). Importantly, the pattern of dual immunoreactivity by such subepithelial cells clearly indicates that they originate from the overlying E-cadherin ϩ non-neural epithelium and that they lose epithelial morphology as a consequence of E-cadherin down-regulation from their cell surfaces.…”
Section: Non-neural Epithelium In the Neural Fold Appears To Be A Sousupporting
confidence: 91%
“…These mechanisms must be even more complex when two or more genes, with distinct expression patterns, are linked in the genome, with the possibility of enhancer crosstalk even greater. Furthermore, it has been shown that gene duplication is usually accompanied by the sharing of enhancers belonging to the protogene, and the specialization of the duplicated genes for individual enhancers, usually resulting in nonoverlapping patterns that when combined cover the entire expression pattern of the original gene (Bruce et al 2001;Locascio et al 2002;de Souza et al 2005). We propose that the regulation of such loci involves additional mechanisms to ensure the correct enhancer-promoter specificity.…”
Section: Promoter-enhancer Equilibriamentioning
confidence: 95%
“…16,17 An obvious example, with respect to the neural crest, is the "swapping" of expression patterns between the paralogous zinc-finger transcription factors slug/snail2 and snail1 in different species. 18 This means that the organismic context of a particular study is critical, since results from one organism may or may not be applicable to others; in this light, it is surprising that in many studies the species examined is not identified explicitly in the abstract! This caveat is worth taking seriously, given that mammals are derived from synapsids, rather than archosaurs, like birds ( Fig.…”
Section: Evolutionary Considerationsmentioning
confidence: 99%